The Effectiveness Test of Fusarium cf. solani as Bioinsecticide for Control of Brown Planthopper and Increasing Rice Productivity - Wiyantono, Anton; Utami, Darini Sri; Ismangil, Ismangil (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
The entomopathogenic fungus Fusarium cf. solani can be used to control brown planthopper. The study aim to obtain the frequency of spraying of the Fusarium cf. solani against brown planthopper at different altitudes. Experiment by planting IR 64 seedlings on plots of 4 m x 4 m, spacing of 25 cm x 25 cm, 10 tons of compost/ha, and 100 % N, P, K. The experiment was carried out with a 2 factors of RCBD. Factor I is land altitude < 100 m above sea level (P1), 100 – 500 m above sea level (P2), and > 500 m above sea level (P3). Factor II is the frequency of spraying the bioinsecticide of the Fusarium cf. solani consisting of no spraying (F0), one time (F1); and twice (F2). Each treatment was made 4 replications. Fungal bioinsecticide concentration Fusarium cf. solani used was 106 spores/ml with a dose of 300 L bioinsecticide/ha. The variables measured were intensity attack, pest population; and yield of rice. Rice yields included the number of productive tillers, fresh plant weight, dry plant weight, percentage of grain content, and soil productivity. The data were analyzed by F test and continued with Duncan's test with 95 % confidence level. The results showed that the frequency of spraying Fusarium cf. solani had no effect on the pest populations, intensity of damage, and production of rice yields. Altitude affects the pest populations, intensity of crop damage, as well as parameters of rice yields. However, there was no interaction between the spraying frequency of Fusarium cf. solani with the height of the experimental site to the experimental parameters.